Analysis of 5S rDNA Arrays in Arabidopsis thaliana: Physical Mapping and Chromosome-Specific Polymorphisms - Cloix, C. (Genome Res, 2000)
A physical map of a pericentromeric region of chromosome 5 containing a 5S rDNA locus and spanning ∼1000 kb was established using the CIC YAC clones. Three 5S rDNA arrays were resolved in this YAC contig by PFGE analysis and we have mapped different types of sequences between these three blocks. 5S rDNA units from each of these three arrays of chromosome 5, and from chromosomes 3 and 4, were isolated by PCR. A total of 38 new DNA sequences were obtained. Two types of 5S rDNA repeated units exist: the major variant with 0.5-kb repeats and one with short repeats (251 bp) only detected on YAC 11A3 from chromosome 3. Although the 38 sequences displayed noticeable heterogeneity, we were able to group them according to their 5S array origin. The presence of 5S array-specific variants was confirmed with the restriction polymorphism study of all the YACs carrying 5S units. [The sequence data described in this paper have been submitted to the EMBL data library under accession nos. AF198182–AF198224.]